Managing rural development : ideas and experience from East Africa - Chambers, Robert (Uppsala : Scandinavian Institute of African Studies, 1974)
This research examines the design and testing of management procedures for use by government servants in rural areas in Kenya carried out in 1971 to 73 in collaboration with Deryke Belshaw of the Overseas Development Group of the University of Norwich.
Includes index.
Includes bibliographical references: p. 165-175.
lje 14/05/2018
Loans
Keywords: Rural development; East Africa